2007
DOI: 10.1016/j.jcp.2006.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Solving Maxwell’s equations using the ultra weak variational formulation

Abstract: We investigate the ultra weak variational formulation for simulating time-harmonic Maxwell problems. This study has two main goals. First, we introduce a novel derivation of the UWVF method which shows that the UWVF is an unusual version of the standard upwind discontinuous Galerkin (DG) method with a special choice of basis functions. Second, we discuss the practical implementation of an electromagnetic UWVF solver. In particular, we propose a method to avoid the conditioning problems that are known to hamper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 21 publications
1
65
0
Order By: Relevance
“…Matching (2.8), (2.9), and (2.10), (2.11), we see that the original UWVF by Cessenat and Després [10] is recovered by choosing α = 1/2, β = 1/2, γ = 0, δ= 1/2. Following [16,17,23], it is also possible to show that the method by Cessenat and Després can also be recovered by writing the second order problem as a first order system, and then discretizing this system by using a discontinuous Galerkin (DG) method with flux splitting approach (classical upwind DG method). Here, we have followed a slightly different approach and cast the UWVF within the general class of DG methods presented in [8].…”
Section: Equation (26) Simply Becomesmentioning
confidence: 99%
“…Matching (2.8), (2.9), and (2.10), (2.11), we see that the original UWVF by Cessenat and Després [10] is recovered by choosing α = 1/2, β = 1/2, γ = 0, δ= 1/2. Following [16,17,23], it is also possible to show that the method by Cessenat and Després can also be recovered by writing the second order problem as a first order system, and then discretizing this system by using a discontinuous Galerkin (DG) method with flux splitting approach (classical upwind DG method). Here, we have followed a slightly different approach and cast the UWVF within the general class of DG methods presented in [8].…”
Section: Equation (26) Simply Becomesmentioning
confidence: 99%
“…This was noted in [15] where it was shown that the UWVF for Maxwell's equations can be derived using discontinuous Galerkin (DG) techniques and a special choice of degrees of freedom. This observation also holds for the Helmholtz equation (see also [9]).…”
Section: Introductionmentioning
confidence: 99%
“…This leads directly and elegantly to the UWVF. In [15] we showed that, in the case of Maxwell's equations, but obviously also for the Helmholtz equation written as a first order system, the UWVF results from a standard upwind discontinuous Galerkin method with a suitable choice of degrees of freedom. Here we give a third, equivalent, derivation using the techniques introduced to unify the analysis of DG methods in [2] because we wish to use methods from the analysis of DG methods to analyze the UWVF.…”
Section: Introductionmentioning
confidence: 99%
“…All these methods are of Trefftz type, namely, they are based on approximation spaces made of functions which are (locally) solutions to the considered PDE. We concentrate, in particular, on the UWVF, which has recently seen rapid algorithmic development and extensions; see [15,23,24,29,[34][35][36], and we would like to analyze its application to the time-harmonic Maxwell equations, considering general Trefftz approximation spaces.…”
Section: Introductionmentioning
confidence: 99%
“…For previous work on the UWVF for Maxwell, we refer to [8,17,19,34]; for different Trefftz-based approaches, we mention [20,47]. Taking cue from the UWVF and following [34], we study a class of Trefftz methods that rely on a DG formulation of the electric field-based Maxwell problem, where the divergence-free constraint is not imposed; the discrete solutions will be elementwise divergence-free, but not globally. Our analysis applies to all these methods, independently of the choice of the particular Trefftz approximation space.…”
Section: Introductionmentioning
confidence: 99%